PREVALENCE OF HYPERTENSION IN TYPE 2 DIABETICS - Maheshwary, Neeta; Naveed, Shabnam; Ali, Zeeshan; Ahmed, Syed Masroor; Yousuf, Ainee Muhammad; ., Sameeta (Pakistan Journal of Physiology, 2016)
Background: Type 2 diabetes and hypertension are important and common chronic diseases that have a huge impact on the health of individuals as well as the health care systems. This study was conducted to estimate the prevalence of hypertension and its associated risk factors among type 2 diabetic patients. Methods: This cross-sectional study was carried out at the Diabetes Clinic, Medical Unit III, Jinnah Postgraduate Medical Centre Karachi from 1st July, 2015 to 31st December, 2015. Two hundred and sixty-two type 2 diabetic patients aged 18 to 80 years were selected using non purposive convenient sampling technique. Each consenting patient underwent a detailed medical history, physical examination and laboratory assessment for measurement of fasting blood glucose, HbA1c and lipid profile. Hypertension was defined according to AHA criteria. Results: Out of 262 patients 101 (37.8%) were males and 161 (62.2%) were females. Mean age of all patients was 53.03±9.9 years and mean duration of diabetes was 10.07±6.04 years. A total of 187 (72.5%) patients were found out to be hypertensive. Patients with a shorter duration (<10 years) of diabetes (75.7%), obesity (72.6%), and central obesity (77.42%) had higher rates of hypertension. Hypertension was found to be significantly associated with dyslipidemias and presence of central obesity (p<0.05). Conclusion: The prevalence of hypertension was high in diabetics. Among diabetic patients hypertension was significantly associated with dyslipidemias and central obesity. Pak J Physiol 2016;12(1):31–4